2015
DOI: 10.1038/nbt.3290
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified guide RNAs enhance CRISPR-Cas genome editing in human primary cells

Abstract: CRISPR-Cas-mediated genome editing relies on guide RNAs that direct site-specific DNA cleavage facilitated by the Cas endonuclease. Here we report that chemical alterations to synthesized single guide RNAs (sgRNAs) enhance genome editing efficiency in human primary T cells and CD34+ hematopoietic stem and progenitor cells. Co-delivering chemically modified sgRNAs with Cas9 mRNA or protein is an efficient RNA- or ribonucleoprotein (RNP)-based delivery method for the CRISPR-Cas system, without the toxicity assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
953
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 967 publications
(1,016 citation statements)
references
References 25 publications
20
953
2
2
Order By: Relevance
“…They have also enabled several protein-delivery applications, including with antibodies, transcription factors and genome editing nucleases 14,21,45,46 . In primary human haematopoietic stem cells and T cells, for example, it was found that expression of Cas9 nuclease and guide RNA from plasmids was poorly tolerated, while direct delivery of Cas9-sgRNA complexes via electroporation improved efficiency, reduced off-target effects and normalized dosage control 21,46 . Such results highlight a trend towards direct delivery of macromolecules rather than their indirect expression from vectors.…”
mentioning
confidence: 99%
“…They have also enabled several protein-delivery applications, including with antibodies, transcription factors and genome editing nucleases 14,21,45,46 . In primary human haematopoietic stem cells and T cells, for example, it was found that expression of Cas9 nuclease and guide RNA from plasmids was poorly tolerated, while direct delivery of Cas9-sgRNA complexes via electroporation improved efficiency, reduced off-target effects and normalized dosage control 21,46 . Such results highlight a trend towards direct delivery of macromolecules rather than their indirect expression from vectors.…”
mentioning
confidence: 99%
“…Nucleofection or transient transfection ) of a preformed Cas9 ribonucleoprotein complex has also been shown to reduce offtarget effects, enabling DNA-free gene editing in primary human T cells (Schumann et al 2015), embryonic stem cells (Liu et al 2015b), Caenorhabditis elegans gonads (Paix et al 2015), mouse (Menoret et al 2015;Wang et al 2015a) and zebrafish embryos , and even plant protoplasts (Woo et al 2015). The incorporation of specific chemical modifications known to protect RNA from nuclease degradation and stabilize secondary structure can further enhance Cas9 ribonucleoprotein activity (Hendel et al 2015;Rahdar et al 2015). In a clever marriage of genome-editing platforms, the FokI cleavage domain has even been fused to an inactivated Cas9 variant to generate hybrid nucleases that require protein dimerization for DNA cleavage (Guilinger et al 2014b;Tsai et al 2014), theoretically increasing CRISPRCas9 specificity.…”
Section: Crispr-cas9mentioning
confidence: 99%
“…The CRISPR/Cas9 system has many potential applications due to its ability to cut the DNA of any genome at any desired location by introducing the cas9 protein and appropriate guide DNA into a cell [7,8]. The system has the ability for genome editing and gene regulation in many types of organisms facilitating the function elucidation of target genes in biology and diseases.…”
Section: Applications Of the Crispr/cas9 Systemmentioning
confidence: 99%